An experimental study of an inherently-safe, natural circulating, flash-tube type system for a nuclear reactor steam supply concept - Loubser, Karl Albie (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.